Design and Optimisation of a Hub Drive Electrical Motor for an L2 Class Electrical Vehicle for Sustainable Urban Transport Applications - Joss, Andreas (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.